IMPACT OF SCHIZOPHRENIA AND BIPOLAR AFFECTIVE DISORDER ON MARITAL SATISFACTION – A COMPARATIVE STUDY - SRI, PENTAKOTA DIVYA; RAJU, T SURYANARAYANA; BOYA, VARADARAJULU; GOTTUMUKKULA, VAIDYANATH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: To compare marital satisfaction among patients with Schizophrenia and bipolar affective disorder. Methods: A cross-sectional study was conducted for 1 month. The sample was chosen by using purposive random sampling, 60 married patients with Schizophrenia and Bipolar Affective Disorder who fulfilled the ICD 10 criteria for Schizophrenia and Bipolar Affective Disorder, respectively, under remission with Clinical Global Impression-Severity Scale (CGI-S) score ≤2, and were assessed for Marital Satisfaction with The Couples Satisfaction Index (CSI) and its relationship with forgiveness is studied with the Marital Offence-Specific Forgiveness Scale (MOFS). Results: Compared to patients with Bipolar Affective Disorder, patients with Schizophrenia reported poor marital satisfaction. Conclusion: It is the first study in India to compare marital satisfaction in patients with Schizophrenia and Bipolar Affective Disorder. The present study suggests that marital satisfaction is more impaired in Schizophrenia patients compared to bipolar affective disorder patients.